Directly absorbing Therminol-Al2O3 nano heat transfer fluid for linear solar concentrating collectors. (1st November 2016) - Muraleedharan, M.; Singh, H.; Suresh, S.; Udayakumar, M.
Highlights: Al2 O3 -Therminol®55 nano heat transfer fluid (nHTF) experimentally characterised. Thermal conductivity enhanced by 11.7% for 0.1 vol% Al2 O3 nanoparticles (NPs). Maximum absorbance occurred at higher wavelengths as NP concentration increased. Solar concentrator delivered heat at 132.8 °C at a thermal efficiency of 62.7%. Directly absorbing nHTFs can lead to the development of next generation solar concentrators. Abstract: This paper reports experimentally measured thermal and optical properties of Al2 O3 -Therminol®55 nano heat transfer fluid (nHTF) in conjunction with a specially developed line focusing Fresnel lens based solar thermal concentrator. Solar collector tests were conducted under real life outdoor ambient and solar radiation conditions. A range of volumetric proportions of Al2 O3 (0.025–0.3 vol%) have been covered. Highest thermal conductivity and refractive index were measured for nHTF with 0.1 vol% concentration of Al2 O3 with higher concentrations (>0.1 vol%) concluded to be unfit for their use in the solar collector applications due to likely agglomeration and sedimentation in the hours of low or nil sunshine when fluid is not circulating. Thermal conductivity enhanced by 11.7% for 0.1 vol% Al2 O3 concentration nHTF. A highest temperature of 132.8 °C was delivered by the solar collector using 0.1% concentration Al2 O3 nHTF at a flow rate of 0.5 lps. This was 44.7 °C higher than that achieved by pure Therminol®55 (88.1 °C) even though the DNI during 0.1% nHTF test was considerably lower than that for the later. The solar concentrator thermal efficiency increased with the proportion of NPs attaining a maximum of 52.2% for 0.1 vol% Al2 O3 nHTF. Directly absorbing nHTFs along with the solar collector developed in this study are predicted to be strong candidate to replace conventional metallic tube receiver using concentrators due to advantages of size compaction and higher thermal conversion efficiency.